Analisis Pasang Surut di Perairan Sungai Musi Menggunakan Metode Least Square (Studi Kasus Intake Air Baku Sistem Gandus Kota Palembang) - Agus Saputra; Taufik Ari Gunawan; Imroatul Chalimah Juliana (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2021)
The tides, which affect the water level of the Musi River causes some problems to occur in Palembang City. One of the main problems related to the tides of the Musi River, especially the low tide, is the failure of the raw water intake building of Regional Drinking Water Company (PDAM) Tirta Musi, Palembang City to operate. At a certain time the river water level recedes, the minimum water level entering the intake pump room is lower than the safe level for the pump to run. In this study, an analysis of the tides of the Musi River was carried out using the Least Square method to evaluate the design of the raw water intake building for the Gandus system to disclose whether it meets the minimum elevation requirements for pump operation. The field observations of the tides were carried out for 15 days for every 1 hour to obtain the primary data for this study using the Hobo Water Meter. The results of this study indicate that the type of the tides in the location of the study is a mixed tidal type with a Formzahl Value of 2.01. 4. Against the design plan of the gandus system of raw water intake, there is a chance that the elevation of the river water level is at 0.5 m from the end of the pump suction pipe, in which the pump cannot function.